Soluzioni innovative per il mobile mapping - Sistemi Avanzati Srl, Sistemi Avanzati Srl (GEOmedia, 2009)
Sistemi Avanzati presents three innovative solutions for mobile mapping Earthmine, the metric evolution of Google Street View, uses a stereoscopic panoramic sensor and 3D vision algorithm to generates 360 degrees images where any point is geo-tagged with its 3D coordinates. Imajing is a portable, easy to use, low cost, video mapping system combining high resolution camera, IMU, barometer, control unit, user friendly software, that enables the final user to directly perform his road survey campaign. Ike1000 is the world's first truly integrated data-capture-device that combines GPS with camera, 3D compass, rangefinder, allowing remote GPS measurement and acquisition of images geotagged (lat, long and alt) on the target coordinates.